(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the article highlights the fact that human rights are the highest value, the fundamental rights and freedoms of a person must be protected and guaranteed by the state, and Uzbekistan’s commitment to international obligations in the field of human rights is emphasized.